The Structure of Empathy - Deonna, Julien (Journal of moral philosophy, 2007)
Abstract If Sam empathizes with Maria, then it is true of Sam that (1) Sam is aware of Maria's emotion, and (2) Sam ‘feels in tune’ with Maria. On what I call thetransparency conception of how they interact when instantiated, I argue that these two conditions are collectively necessary and sufficient for empathy. I first clarify the ‘awareness’ and ‘feeling in tune’ conditions, and go on to examine different candidate models that explain the manner in which these two conditions might come to be concomitantly instantiated in a subject. I dismiss what I call theparallel and oscillation models for not satisfying the transparency condition, i.e. for failing to capture that, if Sam empathizes with Maria, then Sam's own emotional experience towards the object of Maria's emotion has to be mediated by Maria's own emotional experience. I conclude in favour the fusion model as the only model capable of satisfying the transparency condition, and I argue that the suggested proposal illuminates the difference between it and other ways in which we understand the emotions of others. Finally, I expand and clarify the conception of empathy as transparency through responses to obvious objections that the view raises.